The Effect of Using Social Media, Entrepreneurship Education in Increasing Student Entrepreneurial Intentions - Ridhali Raja Mandadwika (SEAN Institute, 2022)
Entrepreneurship is considered as one of the effective solutions in efforts to reduce the high unemployment rate in Indonesia. This study aims to examine the effect of social media, entrepreneurship education and academic support on entrepreneurial intensity. This research was conducted on Islamic Criminal Law 4A students at the Negri Islamic University of North Sumatra to complete the Entrepreneurship semester final exam assignment. The type of research in this research is quantitative. The managerial implications of the research results suggest educational institutions to consider entrepreneurship education and academic support as important enough factors to encourage student interest in entrepreneurship. In the educational process, the problem of cultivating enthusiasm for carrying out the process of entrepreneurial activity is important. An educator must be innovative in relation to growing interest in participating in entrepreneurial activities. In entrepreneurial activity, interest plays an important role so that this aspect must appear before other aspects grow. Each teacher is expected to be able to provide inserts of this content when carrying out the education and learning process.